Dynamics of Representations about Moral Person in Sakha Adolescents (2002-2017) - Eliseeva, Natalia D. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ psikhologii͡a︡ i pedagogika, 2019)
High rates of social and economic changes actualize the problem of morality in modern society. Currently, the psychology of morality has taken shape in a separate scientific research area. The study of the problem of morality in the framework of its cultural understanding, the analysis of the dynamics of ideas about the morality within the culture is of particular relevance. The aim of the current research is to study the dynamics of the implicit representations of the Sakha adolescents about a moral person in the period from 2002 to 2017. It was assumed that there had been no significant changes in the implicit representations for 15 years. In total, 522 people took part in the study, including the preparatory stage. The samples of the first (2002) and second (2017) sections were equalized by gender and age (112 adolescents 14-17 years old, including 49 boys, 63 girls). The study was conducted in the same localities of the Republic of Sakha (Yakutia). The method proposed by the Japanese researchers H. Azuma and K. Kashiwagi, the original questionnaire compiled on the basis of descriptors of the studied culture, was used for the diagnosis. In addition, for a qualitative study of the implicit representations, the analysis of actions that prove the morality of the described person was carried out. The results were processed using factor and content analysis. It has been established that the most stable are implicit ideas about mutual aid and support, respect for the social and natural world, the importance of traditions and the preservation of the “culture of silence”. It is assumed that the family plays an important role in maintaining the stability of moral values. The differences are manifested in the fact that in the content characteristics of the implicit representations the emphasis is shifting from the peculiarities of the interaction with the outside world to the manifestation of personal qualities.